Experiences of barriers and facilitators in mental health care transitions: A qualitative exploration of perspectives from transitional-aged youth, family, and service providers (part 1) - Roula Markoulakis; Hinaya Cader; Karen Wong; Sugy Kodeeswaran; Tracey Addison; Cathy Walsh; Jocelyn Charles; Amy Cheung; Deepy Sur; David Willis; Anthony Levitt (Health Care Transitions)
Introduction: Transitional-aged youth (TAY) are at a vulnerable stage of their development in which mental health and/or addiction (MHA) issues tend to manifest and/or increase in severity. TAY also tend to find themselves subject to multiple care transitions, often resulting in sub-optimal access to MHA services. The objective of this study was to explore the perspectives of TAY, family members, and system providers regarding the supports needed by TAY and their families during transitions through MHA care. Methods: This is a descriptive qualitative study of TAY, family, and provider perspectives on their experiences with accessing/providing MHA care and transition supports for TAY. Focus groups and interviews were conducted with 14 TAY, 26 family members, and 23 service providers. Participants were asked about their experiences with regard to barriers and facilitators to transitions in care for TAY with MHA concerns. Data was analyzed utilizing a thematic analysis approach. Results: Six themes emerged during data analysis: pathways to care, appropriate and comprehensive care, continuity of care, informed care, family involvement, and TAY involvement. These results provide a better understanding of the needs of TAY and their families in relation to accessing and transitioning through MHA system supports and improving MHA outcomes. They also include the views of service providers on the current state of access to and transitions through MHA care, specifically for the TAY population. Discussion: This information reveals the supports needed by TAY and their families along with the challenges created due to a lack of guidance, transition preparation, collaboration, and continuity in the MHA system. MHA providers working with TAY and families can utilize these findings to promote effective TAY and family engagement for positive transitions and care experiences.